Arterial Stiffness and Cardiorespiratory Fitness Are Associated With Cognitive Function in Older Adults. Issue 1 (14th January 2022) - Mason, Justin R.; Tenenbaum, Gershon; Jaime, Salvador; Roque, Nelson; Maharaj, Arun; Figueroa, Arturo
Abstract: Age-related cognitive impairment has been associated with arterial stiffening and decreased cardiorespiratory fitness. The aims of this cross-sectional study were to compare cognitive function domains and cardiovascular parameters in older adults (≥ 65 years old) with high and normal aortic stiffness (via carotid-femoral pulse wave velocity, cfPWV) and to explore relationships among cfPWV, carotid intima-media thickness, cardiorespiratory fitness, and cognitive function. Vascular and cognitive function were measured in older adults with either normal or high cfPWV. Cognitive function was measured via an intensive one-time neuropsychological battery, while cfPWV by applanation tonometry, carotid intima-media thickness and function (i.e., distensibility) by ultrasonography, and cardiorespiratory fitness (i.e., VO2 peak) by a submaximal exercise test. Correlations among age, VO2 peak, carotid intima-media thickness, cfPWV, and cognitive function were performed along with a series of multivariate analyses of variance. Compared with NAS, participants with HAS had greater aortic, carotid, and brachial blood pressures but similar cardiorespiratory fitness and carotid intima-media thickness and distensibility. Participants with NAS exhibited better neuropsychological performance in executive function and attention and overall cognitive function than those with HAS. When controlling for age, visual scanning and perception scores were correlated with cfPWV and VO2 peak. Our findings suggest that certain cognitive domains for older adults are associated with their cardiorespiratory fitness and aortic stiffness.